Ketahanan beberapa varietas jagung (Zea mays L.) terhadap penyakit karat daun (Puccinia sorghi) di Dusun Copti Distrik Prafi Kabupaten Manokwari - Rein Ruimassa; Eko Agus Martanto; Derek Kornelis Erari; Alexander Yaku (Agrotek, 2022)
Common corn rust disease caused by the fungus Puccinia sorghi, causes small spots on the upper and lower surfaces of the leaves which then spread to the entire leaf surface, causing a decrease in photosynthetic yield. Losses due to this disease are 45-60%. This study aims to explore the resistance of corn varieties to rust disease. This research was arranged in a descriptive research design using 240 plants of corn. The maize varieties tested were Pertiwi 3, Betrass, Bissi 2, Bissi 18, Bima, and Prafi Merah varieties. The results showed that the intensity of disease increased continuously every week from the first appearance of 5 WAP to 11 WAP. At 11 WAP the severity of the disease was 76% Pertiwi 3, Betrass 91%, Bissi 2 82%, Bissi 18 89%, Bima 80% and Prafi Merah 92% so that all test varieties were classified as susceptible varieties. The susceptibility was triggered by the test variety's gene system which was not sufficient to inhibit the rate of development of pathogens with high virulence. In addition, weather factors with rainfall ranging between 73and 90%, adequate optimal temperatures ranging between 25.7oC and 28.8oC and heavy rains that occur continuously for 24-26 days strongly support production and sporadic distribution in the crop resulting in an increase in severity disease.